PENGENALAN MAKANAN TRADISIONAL KUE BALOK PANDEGLANG MELALUI KEGIATAN COOKING CLASS PADA ANAK USIA 4–5 TAHUN - Cahya Kamila; Isti Rusdiyani; Dina Kusuma Wardhani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the fading introduction of local culture, especially traditional culinary, among early childhood due to the rapid flow of globalization. Kue balog is a traditional food typical of Pandeglang Regency made from cassava which has not been optimally introduced to the younger generation from an early age. The purpose of this study is to describe the implementation of cooking class activities as a fun and meaningful learning medium, analyze the integration of local culture in cooking class activities to foster children's appreciation of regional culture, and identify plans, methods, strategies, evaluations, obstacles, and solutions in the implementation of cooking class activities to introduce Pandeglang block cakes to children aged 4–5 years at the Pandeglang Pembina State Kindergarten. The research uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. Data analysis refers to the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawn. The validity of the data was tested through source triangulation and triangulation techniques. The results of the study showed that: (1) cooking class activities were proven to be effective as a fun and meaningful learning medium through three structured stages, namely planning, implementation, and evaluation with a learning by doing approach; (2) the integration of local culture is carried out in a planned manner through the introduction of block cakes as the culinary identity of Pandeglang, so that children show awareness and pride in their regional culture; (3) The learning by doing and project-based learning methods with demonstration strategies, individual mentoring, and positive reinforcement have proven to be effective, while obstacles in the form of differences in children's fine motor skills are overcome through individual guidance. Overall, cooking class activities have proven to be effective as a means of introducing traditional foods as well as instilling a love for local culture from an early age.